At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To determine the discontinuity and zero of the function [tex]\( f(x) = \frac{3x^2 + x - 4}{x - 1} \)[/tex], we need to perform the following steps:
1. Find the Discontinuity:
The discontinuity of the function occurs when the denominator is equal to zero, as this would make the function undefined. For the function [tex]\( f(x) = \frac{3x^2 + x - 4}{x - 1} \)[/tex], let's set the denominator [tex]\(x - 1\)[/tex] equal to zero and solve for [tex]\(x\)[/tex]:
[tex]\[ x - 1 = 0 \][/tex]
[tex]\[ x = 1 \][/tex]
Thus, there is a discontinuity at [tex]\(x = 1\)[/tex]. Substituting [tex]\(x = 1\)[/tex] into the original function, we encounter an undefined result since the denominator becomes zero. Therefore, the function is discontinuous at [tex]\(x = 1\)[/tex].
To confirm, we see that when substituting [tex]\( x = 1\)[/tex] into [tex]\(f(x)\)[/tex]:
[tex]\[ f(1) = \frac{3(1)^2 + 1 - 4}{1 - 1} = \frac{3 + 1 - 4}{0} = \frac{0}{0} \][/tex]
This indicates an undefined value or a discontinuity at [tex]\(x = 1\)[/tex].
2. Find the Zeroes of the Function:
To find the zeroes of the function, we set the numerator equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ 3x^2 + x - 4 = 0 \][/tex]
Solving this quadratic equation using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex] where [tex]\(a = 3\)[/tex], [tex]\(b = 1\)[/tex], and [tex]\(c = -4\)[/tex]:
[tex]\[ x = \frac{-1 \pm \sqrt{1^2 - 4 \cdot 3 \cdot (-4)}}{2 \cdot 3} \][/tex]
[tex]\[ x = \frac{-1 \pm \sqrt{1 + 48}}{6} \][/tex]
[tex]\[ x = \frac{-1 \pm \sqrt{49}}{6} \][/tex]
[tex]\[ x = \frac{-1 \pm 7}{6} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{-1 + 7}{6} = \frac{6}{6} = 1 \][/tex]
[tex]\[ x = \frac{-1 - 7}{6} = \frac{-8}{6} = -\frac{4}{3} \][/tex]
Therefore, the zeroes of the function are [tex]\(x = 1\)[/tex] and [tex]\(x = -\frac{4}{3}\)[/tex].
3. Determine the Correct Pair:
Given the discontinuity at [tex]\(x = 1\)[/tex], we need to find the zero that corresponds to one of the given answer choices. We already see that [tex]\(x = -\frac{4}{3}\)[/tex] is one of the roots:
[tex]\[ \left(-\frac{4}{3}, 0\right) \][/tex]
Given the detailed analysis, the correct answer pairs the discontinuity and zero correctly as:
Discontinuity at [tex]\((1, \text{undefined})\)[/tex] since the function is undefined at [tex]\(x = 1\)[/tex], zero at [tex]\(\left(-\frac{4}{3}, 0\right)\)[/tex].
Among the provided options, the correct one is:
Discontinuity at [tex]\((1,7)\)[/tex], zero at [tex]\(\left(-\frac{4}{3}, 0\right)\)[/tex].
[tex]\[ \boxed{\text{Discontinuity at } (1,7), \text{ zero at } \left(-\frac{4}{3}, 0\right)} \][/tex]
1. Find the Discontinuity:
The discontinuity of the function occurs when the denominator is equal to zero, as this would make the function undefined. For the function [tex]\( f(x) = \frac{3x^2 + x - 4}{x - 1} \)[/tex], let's set the denominator [tex]\(x - 1\)[/tex] equal to zero and solve for [tex]\(x\)[/tex]:
[tex]\[ x - 1 = 0 \][/tex]
[tex]\[ x = 1 \][/tex]
Thus, there is a discontinuity at [tex]\(x = 1\)[/tex]. Substituting [tex]\(x = 1\)[/tex] into the original function, we encounter an undefined result since the denominator becomes zero. Therefore, the function is discontinuous at [tex]\(x = 1\)[/tex].
To confirm, we see that when substituting [tex]\( x = 1\)[/tex] into [tex]\(f(x)\)[/tex]:
[tex]\[ f(1) = \frac{3(1)^2 + 1 - 4}{1 - 1} = \frac{3 + 1 - 4}{0} = \frac{0}{0} \][/tex]
This indicates an undefined value or a discontinuity at [tex]\(x = 1\)[/tex].
2. Find the Zeroes of the Function:
To find the zeroes of the function, we set the numerator equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ 3x^2 + x - 4 = 0 \][/tex]
Solving this quadratic equation using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex] where [tex]\(a = 3\)[/tex], [tex]\(b = 1\)[/tex], and [tex]\(c = -4\)[/tex]:
[tex]\[ x = \frac{-1 \pm \sqrt{1^2 - 4 \cdot 3 \cdot (-4)}}{2 \cdot 3} \][/tex]
[tex]\[ x = \frac{-1 \pm \sqrt{1 + 48}}{6} \][/tex]
[tex]\[ x = \frac{-1 \pm \sqrt{49}}{6} \][/tex]
[tex]\[ x = \frac{-1 \pm 7}{6} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{-1 + 7}{6} = \frac{6}{6} = 1 \][/tex]
[tex]\[ x = \frac{-1 - 7}{6} = \frac{-8}{6} = -\frac{4}{3} \][/tex]
Therefore, the zeroes of the function are [tex]\(x = 1\)[/tex] and [tex]\(x = -\frac{4}{3}\)[/tex].
3. Determine the Correct Pair:
Given the discontinuity at [tex]\(x = 1\)[/tex], we need to find the zero that corresponds to one of the given answer choices. We already see that [tex]\(x = -\frac{4}{3}\)[/tex] is one of the roots:
[tex]\[ \left(-\frac{4}{3}, 0\right) \][/tex]
Given the detailed analysis, the correct answer pairs the discontinuity and zero correctly as:
Discontinuity at [tex]\((1, \text{undefined})\)[/tex] since the function is undefined at [tex]\(x = 1\)[/tex], zero at [tex]\(\left(-\frac{4}{3}, 0\right)\)[/tex].
Among the provided options, the correct one is:
Discontinuity at [tex]\((1,7)\)[/tex], zero at [tex]\(\left(-\frac{4}{3}, 0\right)\)[/tex].
[tex]\[ \boxed{\text{Discontinuity at } (1,7), \text{ zero at } \left(-\frac{4}{3}, 0\right)} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.